Optical Waveguide‐Enhanced Diffraction for Observation of Responsive Hydrogel Nanostructures. Issue 6 (30th January 2017) - Pirani, Federica; Sharma, Nityanand; Moreno‐Cencerrado, Alberto; Fossati, Stefan; Petri, Christian; Descrovi, Emiliano; Toca‐Herrera, José L.; Jonas, Ulrich; Dostalek, Jakub
Abstract : In situ optical diffraction observation of swelling and collapsing of responsive photo‐crosslinked N ‐isopropylacrylamide hydrogel arrays of nanopillars is reported. Unusual properties associated with bending of nanopillars, erasure of the topographic structure by drying below the lower critical solution temperature (LCST), and recovery by subsequent swelling below the LCST and drying at temperature above the LCST are observed. Abstract : Optical diffraction measurements are reported for in situ observation of swelling and collapsing of responsive hydrogel nanostructures. The optical signal is enhanced by probing the surface carrying periodic arrays of hydrogel nanostructures by resonantly excited optical waveguide modes. UV‐nanoimprint lithography is employed for the preparation of the arrays of nanopillars from photo‐crosslinked N ‐isopropylacrylamide (pNIPAAm)‐based hydrogel that are covalently tethered to a gold surface. The thermo‐responsive properties of such pNIPAAm nanopillars that swell in 3D are compared to those of a thin film prepared from the identical material and that is allowed to swell predominantly in 1D. The nanopillars with a diameter of ≈100 nm and aspect ratio of 2 swell by a factor of ≈6 as determined by optical measurements supported by simulations that are compared to morphological characteristics obtained from atomic force microscopy. Bending of nanopillars above the lower critical solution temperature (LCST), erasure of the topographic structure by drying at temperature below the LCST, and recovery by subsequent swelling below the LCST and drying at temperature above the LCST are observed.